2014
DOI: 10.1021/am501379m
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of 1D ZnO@TiO2Core–Shell Nanostructures for Enhanced Photoelectrochemical Water Splitting under Solar Light Illumination

Abstract: A fast and low-cost sol-gel synthesis used to deposit a shell of TiO2 anatase onto an array of vertically aligned ZnO nanowires (NWs) is reported in this paper. The influence of the annealing atmosphere (air or N2) and of the NWs preannealing process, before TiO2 deposition, on both the physicochemical characteristics and photoelectrochemical (PEC) performance of the resulting heterostructure, was studied. The efficient application of the ZnO@TiO2 core-shells for the PEC water-splitting reaction, under simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
122
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(130 citation statements)
references
References 57 publications
6
122
0
Order By: Relevance
“…TiO 2 /ZnO coreshell nanomaterial presents a high interest due to its potential applications, such as optoelectronic device [3,4], dye-sensitized solar cells (DSSCs) [5], and photocatalysis [6][7][8]. Recently, TiO 2 /ZnO core-shell nanomaterial was used for photocatalytic H 2 production through water splitting [9]. TiO 2 nanomaterial presents interest due to its potential applications in the field of photovoltaics, gas sensors, dye-sensitized solar cells (DSSCs), etc.…”
Section: Introductionmentioning
confidence: 99%
“…TiO 2 /ZnO coreshell nanomaterial presents a high interest due to its potential applications, such as optoelectronic device [3,4], dye-sensitized solar cells (DSSCs) [5], and photocatalysis [6][7][8]. Recently, TiO 2 /ZnO core-shell nanomaterial was used for photocatalytic H 2 production through water splitting [9]. TiO 2 nanomaterial presents interest due to its potential applications in the field of photovoltaics, gas sensors, dye-sensitized solar cells (DSSCs), etc.…”
Section: Introductionmentioning
confidence: 99%
“…Various development approaches for efficient materials and well-designed device structures have been investigated to achieve enhanced power conversion efficiency (PCE) of HPV devices [5,6]. Among the developed nanomaterials, ZnO nanorod arrays, which can be grown vertically from a substrate, have great potential for HPV applications because of their ease of synthesis [7,8] and high electron mobilities (*10 2 cm 2 V -1 s -1 ) [9] with a direct transport pathway to the electrode [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…It also has been found that a red shift occurs, as immersion time increased, causing an increase on the amount of zinc oxide [34]. In addition, the red shift might also be due to the change in the crystal phase composition of TiO 2 [22][23][24][25][26][27][28].…”
Section: Resultsmentioning
confidence: 97%
“…As a result, it still posts a long-standing challenge to resolve these fundamental disadvantages for diverse aspects of photocatalytic applications. To solve these problems, researches have been proliferated to reinforce the photocatalytic properties by manipulating nanostructures or morphologies of TiO 2 and ZnO [14][15][16][17][18][19][20][21][22][23][24][25]. In these cases, of particular note is the coupling of TiO 2 and ZnO that has been well established to remarkably enhance the separation efficiency of photoexcited charge carriers because of the formation of heterojunction structure between them, thus boosting quantum efficiency and photostability of the hybrid photocatalyst [14].…”
Section: Introductionmentioning
confidence: 99%